Self-similarity of pressure profiles during forced granular flows - Ferreyra, María Victoria (2024)
We present measurements of the vertical stress profile σ on the base of flat-bottomed cylindrical silos discharged through an orifice centered on its base. An overweight forces the material on top of the free surface. The mean bottom pressure σ(z,D,W), with z the height of the granular column, D the silo diameter, and W the mass of the overweight, increases significantly at the end of the discharge. Inspired by early models of stress distribution, we show that σ measured at z=0 can be rescaled to yield a collapse of the data, as a function of z/D, for all D and W explored. We also show that the profile σ(r) is self-similar as a function of the radial coordinate r and can be rescaled to collapse the data for different z,D, and W. Although the model correctly predicts the functional dependences, it fails in quantitative terms. These results challenge our understanding of free and forced granular flows through orifices.